ANALISIS PENGARUH EFISIENSI MODAL KERJA DAN STRUKTUR ASET TERHADAP PROFITABILITAS PADA INDUSTRI SEMEN YANG TERCATAT DI BEI - B31108069, Risma Dewi (Jurnal Manajemen Update, 2013)
This study was conducted to look into the effect of the cash conversion cycle and the asset structure of the company towards profitability. the results of test methods can be concluded that the independent variables had a significant effect on the ROA dependent variable. Two independent variables namely CCC and the RCAFA has a very close relationship to the dependent variable. Between CCC with ROA were found to have a positive correlation, and RCAFA and with ROA were found to have a negative correlation. SPSS output of the results did not reveal any problems deviation classical assumption that the problem multicollinearity, autocorrelation problem, and the problem heterocedastity. So the results of multiple regression linear models in companies engaged in the cement industry could be said to be good, there are no significant problems. Keywords: -, cash conversion cycle (CCC), RCAFA, ROA, descriptive test, t-test, f-test, coefficient of determination, Pearson correlation, and test the assumptions of classical aberrations